(untitled) (Philological Studies, 2019)
The dichotomy, or the ambivalence of the literary system, presents a basis for this research paper, which aims at portraying the two constitutive models of literature, i.e., the written and the oral model. The former one is often acknowledged as exclusive, sophisticated, refined and intellectual, versus the latter, as its inversion, plebeian, inclusive, crude and illiterate. Our goal will be to show the inaccuracy of this axiological treatment.